Investigation Of The Effect Of The Cast Booster With Cumulative Effect On Arrays With The Presence Of Solid Inclusions - Mollova, Zdravka (Wroclaw University of Technology, 2024)
The object of research in the present article is the intensification of the fragmentation of mas-sifs with hard inclusions, by means of dispersed and additional drilling, using cast boosters with cumulative lining. The article presents the obtained dependences of the change in the depth of destruction of solid inclu-sions, depending on the length of the cumulative jet, its density and the strength of the solid inclusion, which allow to develop a methodology for engineering calculation of the parameters of the drilling-explosive works and the sequence of initiating the charges. The use of cast boosters with a cumulative -funnel, located in the lower part of the borehole, allows, at the expense of managing the action of the blast energy on the lower layers of the blasted massif, to reduce the average size of the fragments by 7.9% and by 1.6 times the resulting oversized fractions.
Mining Science, Vol. 31, 2024, s. 249-257
Keywords: mining; geology; geo-engineering